Deliberate self harm patients with depressive disorders: treatment and outcome. - Haw, C; Houston, K; Townsend, E; Hawton, K (2002)
BACKGROUND: Depression is the most common psychiatric disorder in deliberate self-harm (DSH) patients and in those who commit suicide. The aim of this study was to examine the treatment received by DSH patients with depression and their progress following DSH. METHODS: A representative sample of 106 patients with an ICD-10 depressive episode who presented to a general hospital following an episode of DSH were investigated in terms of their treatment before and after the episode and their outcome at follow-up. RESULTS: Prior to the index episode of DSH, 39 patients (36.8%) were receiving treatment from the psychiatric services and a further 35 (33.0%) were receiving treatment for mental health problems from their general practitioner. Fifty-two patients (49.1%) were receiving antidepressants (in therapeutic dosages in 93.6%). After the episode of DSH 94 patients (88.7%) were offered treatment with the psychiatric services, either as a new referral or continuation of treatment they were receiving prior to DSH. Of the patients who were followed-up, 36.3% remained in contact with the psychiatric services, 52.3% showed poor compliance with recommended treatment and 60.2% no longer fulfilled the diagnostic criteria for depression. Almost one-third reported a further episode of DSH during the follow-up period. LIMITATIONS: The nature and quality of non-physical treatments provided by the psychiatric services was not investigated. Reports of the treatment provided by general practitioners, the timing of improvement in symptoms and compliance with treatment largely relied on patients' self report. CONCLUSIONS: All patients presenting following DSH need to be carefully screened for depressive illness. Randomised controlled studies need to be conducted on DSH patients with depression to determine which treatments are effective.